Fantastika in sodobni slovenski roman ob koncu stoletja - Zupan Sosič, Alojzija (Jezik in slovstvo, 2001)
Fantasy in the Slovene novel at the end of the 20th century is related to genre and thematic impluses. The 1990s witnessed an upsurge of several fantasy genres (the fairy tale, the anti utopian novel and horror novel) as well as of regional fantasy novels. The latter thematized quaintness of peripherial Slovene regions, viz. Istria, Prekmurje, and Prlekija.
Keywords: Slovene literature; slovenska književnost; novel; roman; fantastika